Validity Of Physical Test Items Skates Sports Branch East Java Regional Training Center 100 - Muhammad Oky Andrianto; Toho Cholik Mutohir; Irmantara Subagio; Moh Amrullah Albaitomi (UNIVERSITAS NEGERI MAKASSAR, 2024)
Roller skating competition is one of the sports competitions that slide at a certain speed using shoes that have wheels on the bottom as a means. Roller skating is a branch of sport that requires prime physical condition. The right form of Physical Test will help analyze which physical components need to be improved in supporting the ability to compete in roller skating. This study aims to analyze the validity of the items of the roller skating physical test and how much influence it has on the technique for East Java roller skating. This study is a non-experimental type of Quantitative Development Research, namely development research with a correlational design model. The sampling technique used the purposive sampling method for 10 male and female roller skating athletes from East Java. From the 10 athletes, physical test data were taken and then analyzed using factor analysis, reliability testing and multiple regression testing with the help of the SPSS statistical program. The results of the study showed that out of 12 physical items after being analyzed, only 6 items were declared valid and could be analyzed. The results of the Extraction value showed that all items had a value of >0.5 or 50%. For the results of the PCA extraction, the factor formed was 1 with an eigenvalue of 5,063. Then the results of the reliability test showed a value of 0.868 > 0.60. For the results of the Multiple Regression Test, the R Square value showed a value of 0.960 or equal to 96% with Details of the contribution of effective influence on the 6th roller skates. The variables are chin up 2%. Vertical Jump 29%, Triple Jump 29%, Peak power 7%, Wattbike 28% and Single Leg Squat 2%.